(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article deals with the general concepts of innovation and investment activity, describes the structure and components of the state policy regarding the implementation of innovation and investment changes, the role and significance of innovation and investment processes in gas transport enterprises are determined. The factors of internal and external influences on the formation of innovation and investment environment of gas transport enterprises are analyzed. The theoretical and practical directions in improving the social and organizational effect at the enterprises of the gas transportation sphere on the basis of innovation-investment principles are outlined.